Advanced MRI Patterns of Muscle Disease in Inherited and Acquired Myopathies: What the Radiologist Should Know - Caetano, António Proença; Alves, Pedro (Seminars in Musculoskeletal Radiology, 2019)
Myopathies represent a heterogeneous group of skeletal muscle disorders characterized by morphological and functional changes in the muscle, such as replacement of muscle tissue by connective tissue, fatty infiltration, and/or inflammation. They can be classified as hereditary, acquired idiopathic, and secondary myopathies.Diagnosis of hereditary and acquired myopathies is challenging, with often overlapping clinical and pathologic features, and it generally relies on a multimodal approach. Current imaging modalities used in neuromuscular imaging include computed tomography, ultrasound, and magnetic resonance imaging (MRI).Topographical patterns of muscle involvement have been described for several myopathies, and they can be identified using whole-body MRI. Indeed, this technique has proven to be an invaluable tool for diagnostic work-up, guidance of muscle biopsy, and biochemical and genetic investigation, as well as disease monitoring and follow-up.
Keywords: myopathy; neuromuscular disorder; magnetic resonance imaging; muscle